BLOCKCHAIN ADOPTION IN PUBLIC FINANCIAL MANAGEMENT: IMPLICATIONS FOR AUDITABILITY AND TRUST IN GOVERNMENT INSTITUTIONS - Sri Hartati; Novira Fazri Nanda; Arif Nadzirul Haq E (CV. Lafadz Jaya, 2026)
The development of digital technology has driven the transformation of public financial management towards a more transparent, accountable, and efficient system. One innovation that has received significant attention is blockchain, which offers the characteristics of decentralization, transparency, data security, and immutable transaction recording. This study aims to analyze the adoption of blockchain in public financial management and its implications for auditability and increasing public trust in government institutions. The method used is a literature review, examining various scientific articles, research reports, and relevant academic publications regarding blockchain implementation in the public sector. The results of the study indicate that blockchain implementation has the potential to improve audit quality by providing a documented, real-time, accurate, and verifiable transaction trail. Furthermore, this technology can reduce the risk of data manipulation, increase transparency in budget use, and strengthen public oversight mechanisms. Other findings indicate that the increased transparency and accountability resulting from blockchain use contribute positively to building public trust in government institutions. However, blockchain adoption still faces various challenges, such as regulatory limitations, digital infrastructure readiness, human resource competency, and system interoperability issues. This research confirms that blockchain has strategic potential in supporting more accountable and trustworthy public financial governance reforms, but its success requires policy support, strengthening institutional capacity, and the development of an adequate digital ecosystem.